Non-violent communication as a path to subversive rationalization: A social technology transforming public organizations - Pereira de Souza, Mariana Mayumi; Ventola Marra, Adriana (Organizações & Sociedade, 2025)
The aim of this article is to analyze the subversive potential of the technical codes of nonviolent communication (NVC), understood as a social technology, in the bureaucratic management system of a public organization. A qualitative and exploratory study was carried out using the case study method, comparing the perceptions of civil servants who had systematic contact with NVC with those who were unaware of it. The material collected in 16 semi-structured interviews was analyzed using discourse analysis. As a result, we observed that the application of the technical codes of NVC favored self-confidence, self-reflection, and cooperation among individuals, emphasizing the subversive potential of NVC in favor of more dialogical and democratic contexts. NVC brings new technical repertoires on how to proceed in specific situations of interaction, deconstructing or rendering meaningless behavioral patterns rooted in alienating forms of communication. In this way, we believe it is possible to subvert the bureaucratic technical system by introducing new contexts for interaction. Therefore, the research contributes to detailing the application of NVC in organizations, as well as presenting a theoretical-methodological framework that can be used in other discursive analyses, especially in the application of social technologies.